Beyond Lihué Calel National Park: New records for the rarity Gaillardia Cabrerae covas (Asteraceae) (Semiárida, 2023)
Until now, Gaillardia cabrerae Covas has been considered an exclusive endemic species of Lihué Calel, a mountain range system in the center-south of La Pampa and the only National Park in the province. In this work, two new presence sites are recorded outside the limits of the protected area. Through an active search in sites with similar geological characteristics to the known distribution site, a population was identified in the Sierras Chicas and another one in the Choique Mahuida Hills, the latter about 95 km southern Lihué Calel National Park. The condition of rarity and the criteria to be taken into account for the categorization of the species are discussed even when its spatial distribution is now resized. The sites in which G. cabrerae develops represent refuges in which many rare species find particularities of the microsite in order to survive. The vulnerability of the species deserves studies that account for its habitat requirements, emphasizing unprotected populations.
Keywords: Rarity; Gaillardia cabrerae; endemism; Sierras chicas; Sierras de Choique Mahuida; Lihué Calel